2011
DOI: 10.2138/am.2011.3789
|View full text |Cite
|
Sign up to set email alerts
|

Cesium and strontium incorporation into zeolite-type phases during homogeneous nucleation from caustic solutions

Abstract: Formation of faujasite-and sodalite/cancrinite-type phases associated with caustic waste reactions in the environment may structurally incorporate contaminant species such as radioactive Sr 2+ and Cs + , and thus provide a mechanism of attenuation. To investigate mineral evolution and structural incorporation of cations in simplified experiments, aluminosilicate solids were precipitated homogeneously at room temperature from batch solutions containing a 1:1 molal ratio of Si to Al and 10 -3 molal Sr and/or Cs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Additionally, at the Hanford site intentional and unintentional discharges of alkaline tank solutions to the subsurface may have resulted in the formation of pertechnetate-bearing feldspathoid phases. Previous investigations demonstrated that when simulated tank waste reacts with Hanford sediments, a range of feldpathoid phases form including sodalite. , This study provides the data needed to identify the chemical conditions required to maximize TcO 4 – incorporation into sodalite as well as the ability to predict the long-term stability of this phase in environmental systems.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, at the Hanford site intentional and unintentional discharges of alkaline tank solutions to the subsurface may have resulted in the formation of pertechnetate-bearing feldspathoid phases. Previous investigations demonstrated that when simulated tank waste reacts with Hanford sediments, a range of feldpathoid phases form including sodalite. , This study provides the data needed to identify the chemical conditions required to maximize TcO 4 – incorporation into sodalite as well as the ability to predict the long-term stability of this phase in environmental systems.…”
Section: Resultsmentioning
confidence: 88%
“…For example, aluminosilicate sodalites, both natural and synthetic, can vary widely in composition but have the general formula of M 8 (Al 6 Si 6 O 24 )­X 2 , where M is a monovalent cation (such as Cs + , K + , Na + , etc.) and X can vary between monovalent or divalent anions (such as OH – , Cl – , Br – , I – , MnO 4 2– , ReO 4 – , or theoretically TcO 4 – ). …”
Section: Introductionmentioning
confidence: 99%
“…Strontium extended X‐ray absorption fine structure and transmission electron microscopy (TEM)–energy‐dispersive X‐ray spectrometry (EDS) analysis showed that neophases contained Sr and Cs in the HIGH treatments. Strontium was also clearly detected in neo‐phases formed in the LOW treatment, whereas Cs was below EDS detection (Perdrial et al, 2011; Rivera et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Cesium was quite readily desorbed (up to 40% of total Cs in solids), while only 6% of the Sr was released to solution. A reactive transport model (Crunchflow) was developed to describe Sr and Cs release from the previously characterized solid phases (Rivera et al, 2011). Parameter estimation was performed (using the program PEST) to derive a set of selectivity coefficients describing exchange sites on both zeolite and feldspathoid phases, in addition to dissolution of solid HN phases.…”
Section: Homogeneous Nucleation (Hn) Productsmentioning
confidence: 99%
“…(yellow atoms) and typical distances betwwen cations and framework Al (light blue) or Si (dark blue)atoms for a) Sr-exchanged zeolite-X; b) Nasodalite; c) Na-cancrinite. (Rivera et al, 2011) Using a suite of methods (silver thiourea with Cs and Rb competition and flow-through technique with Rb), we measured the density of high affinity sites (HAS) in pristine and hyperalkaline-weathered Hanford sediments exposed to high or low concentrations of Cs, Sr and I for 6 months or 12 months under either CO 2 -free or atmospheric CO 2 conditions. New mineral formation affected HAS density, with hyperalkaline-weathering of these sediments increasing the density of high affinity Cs and Rb adsorption sites relative to pristine Hanford sediments.…”
mentioning
confidence: 99%